Engineering an improved coconut processing in the Philippines at the farm level - Pestano, Lola Domnina B. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The traditional methods of copra processing such as sun drying and direct smoke drying or "tapahan" are stil generally implemented in the Philippines by coconut farmers and manufacturers. These methods produce aflatoxin (and other related toxins) and polycyclic aromatic hydrocarbon (PAH) respectively above permissible levels in copra and in crude coconut oil (CNO) that resulted to very low prices of copra-related products in the world market. The Wijose Process of coconut processing, developed for the production of copra, milk and dietary flour offers solution to many problems besetting the industry with 94.7% recovery of the coconut fruit parts and waste materials. The Wijose wet process focuses on the extraction of primary and secondary milk and recovery of coconut meat residue. Seven mathematical models (Newton, Page, Henderson and Pabis, logarithmic, non-linear decomposition model (NLDM), combined decomposition model (CDM) and modified combined decomposition model (MCDM)) were examined to describe the drying behavior of coconut meat slices at 60, 70, and 80°C using a laboratory dryer at the Ch.E. Laboratory in UP-Diliman and a hot-air batch dryer that was developed to eliminate toxin contaminated copra. The MCDM gave the best fit with high coefficient of determination value. The developed model predicted a drying temperature of 80°C to reach the desired moisture content of 7% wet basis in the shortest drying time of 188.3 min. Solid fuel was produced by torrefaction from coconut farm wastes, particularly dried coconut leaves with a calorific value 27.78 MJ/kg that will be utilized as alternative source of energy in the indirect drying of coconut meat or residue. A coconut processing plant for the production of VCO and dietary flour was developed in a coconut farm plantation in Lutucan I, Sariaya, Quezon based on the conceptual design of the Wijose proces
Thesis (Ph.D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Coconut -- Processing -- Philippine; Coconut product; Wijose proces